The Development of Corruption Risk Management Model for the Ministry of Tourism and Sports - ์Nilavongse, Chaweewan; Sintao, Nittaya; Chaokromthong, Kajohnsak (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
The purposes of this research were to 1) study the corruption risk management process, 2) identify factors affecting the success of the implementation of the corruption risk management policy, and 3) develop a corruption risk management model of the Ministry of Tourism and Sports. Qualitative research methods were used with 15 in - depth interviews and 15 focus group discussions, including 30 key informants. The research results was found that 1) The corruption risk management process of the Ministry of Tourism and Sports should develop a corruption risk management process throughout the organization according to the PDCA (Plan - Do - Check - Act) cycle. 2) Leadership and cooperation were the most critical factors for successful implementation of the corruption risk management policy. Efficiency in planning and control as well as the creation of solidarity or continuity were secondary important factors. 3) There are three model of corruption risk management development as follows: 1) Corruption risk management targeting actions by individuals acting alone often resulting from a weak internal control system. Management of corruption risks By applying the principles of internal control of the COSO (2013) standard, 2) Corruption risk management addressing actions involving both parties including both the giver and the receiver. Management of corruption risks by applying the principles of the ISO 37001 standard as a tool for managing and resisting giving and receiving bribes, and 3) Corruption risk management addressing policy - level projects and the administration of the Thai Tourism Promotion Fund.